Political awareness among students / Shamsinar Rahman and Che Hamdan Che Mohd Razali - Rahman, Shamsinar; Che Mohd Razali, Che Hamdan (Universiti Teknologi MARA Cawangan Pahang, 2019)
Political awareness refers to the political information and political knowledge that someone possessed. Political awareness might be differing from one individual to another. Students is one of the group of individuals that will become the leader of this country in the future. Some students when attaining the age of 21 years old, they are eligible to vote. Therefore, it is very important for them to understand current political system. That is why the Ministry of Education has obliged the Malaysian Studies course to be offered to all IPTS students, which one of the topics that they will learn is the Malaysian Government System. Therefore, it is important for the students to aware of the political matters of their surroundings.